Applying organized skepticism to preprints - Browman, Howard I. (Septentrio Conference Series, 2019)
Watch the VIDEO. A preprint is a scholarly work posted by the author(s) in an openly accessible platform, usually before or in parallel with submission to a peer reviewed publication. While the sharing of manuscripts via preprint platforms has been common for many years in disciplines such as physics and mathematics, uptake in other disciplines had, until very recently, been low. The use of preprints is now growing exponentially. The reasons for this appear to be based on several purported advantages of preprints that have not been thoroughly assessed: low cost (but is it sustainable?); immediate publication; establishes precedence; improves quality of papers pre-submission; eliminates journal hierarchies and inequalities; identifies hypotheses not to test further (by making negative results available); a source of submissions for journals. I will take a skeptical view of these advantages and ask: do preprints really accomplish all of this? I will also present the many disadvantages – even dangers – of preprints as these have not been adequately scrutinized: bypasses peer review allowing documents containing unvetted claims to be made freely available; results in multiple competing versions (all of which are citable) of what – without careful and informed examination – appears to be the same content to persist in perpetuity (the preprint version of which is much more likely to contain errors and unvetted claims); presently, no one is responsible for updating the preprint server version, nor to link it to the final published version.